Determining Customer Satisfaction on Telkomsel Card User in Belopa City, Luwu Regency - Ansri Jayanti; Tasrim Tasrim; Nina Fapari Arif (Institute of Computer Science (IOCS), 2021)
Consumer satisfaction is an individual condition who feels the product's performance. Experience arising from using the product as part of consumer expectations. This expectation will lead to a feeling of hopelessness or dissatisfaction with product performance. This study uses expectation disconfirmation theory as a basis for thinking about customer satisfaction. The population in this study were all Telkomsel users in Belopa City, Luwu Regency, and Province of South Sulawesi with a total sample of 286 people. The sampling method used accidental sampling with a questionnaire as the main data collection tool. The data analysis used multiple linear regression analysis. The results showed that product quality, after-sales service and price perception as determinants of Telkomsel card customer satisfaction.